Early Versus Delayed Presented Patients with Acute Lower Limb Ischemia Undergoing Revasucularization: A Comparison of Limb Salvage Rate - Muhammad Shoaib Khan, Akif Amin, Hafiz Gul Nasib Khan, Nida Jawad, Rabia Gilani, Farah Ali, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To examine the success rate of limb salvage in patients with acute lower extremity ischemia of Rutherford class IIb who presented early vs late and were receiving revascularization Study Design: Comparative/observational study Place and Duration: This study was conducted in multi centers at Mardan Medical Complex and Teaching Hospital and DHQ Battagram during the period from January, 2021 to June, 2022 Methods: 60 patients with acute lower limb ischemia of Rutherford class IIB, ranging in age from 18 to 65, were recruited in this research. Two groups of patients were formed. 35 patients make up Group I (delayed presentation >6 hours), while 25 patients make up Group II (early presentation 6 hours). Embolectomy was performed on each patient. At the third month following surgery, the limb salvage rate in the two groups was compared. P-value 0.05 was considered significant when the data were analyzed using SPSS 22.0. Results: Regarding age and gender, there was no discernible difference between the two groups (p-value >0.05). A substantial difference was seen in the limb salvage rate between the two groups (p-value 0.05), with group I having 22 (62.9%) patients with limb salvage and group II having 21 (84%) patients with limb salvage. When compared to group II, mortality was higher in group I (delayed presentation) (17.1% Vs 0%) with a p-value <0.05. Conclusion: The limb salvage rate was found to be much higher in early-presented patients than in delayed-presented patients. Patients who were presented later than those who were presented earlier had substantially higher 30-day death rates and amputation rates. Keywords: Early Presented, Acute Lower Limb Ischemia, Late Presented, Limb Salvage, Revascularization